The Criminal Law Influence on the Modern Electronic and Information Society of the Russian Federation - Komarov, Anton A.; Dorozhinskaya, Elena A.; Krupnitskaya, Valeria I.; Rozuman, Irina V. (International Review of Management and Marketing, 2016)
The present work is focused on the study of the prospects for further improvement of the territorial and extraterritorial principles of the criminal law in respect of the global information space. When carrying out in Russian judicial and legal reform according to the Constitution of the Russian Federation the problems concerning protection of the rights and personal freedoms, its interests by all law-enforcement system of the Russian Federation are priority. Certainly, considering tendencies of the informatization development of the world public process, the documentalization of criminal procedure has to be carried out by means of electronic and information technologies. The main result of our study was made by building a set of recommendations of criminal law relating to the institution of the criminal law. However, it is obvious that the criminal law in time and space is made by a few different rights institutions. Therefore, in the first case we receive the formal answer to the question: what law is the subject to application; and in the second – on whom does its action extend. Keywords: internet, information society, criminal law, jurisdiction, electronic society JEL Classifications: K14, K40, K49